2023
DOI: 10.1590/s1983-41952023000200010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prehydration of Portland cement on the superplasticizer consumption and the impact on the rheological properties and chemical reaction

Abstract: The use of pre-hydrated cement in formulation of mortar and concrete is common because there is not always effective control on the cement production, grinding, transportation and subsequent storage. This paper presents a case study on the optimization of admixture for use with prehydrated cement by assessing changes in the rheological properties of Portland cement artificially pre-hydrated. The cement was artificially pre-hydrated by exposure to relative humidity (RHs) of 90%, in an environment of NH4Cl satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…They also attribute these coatings to the lower values observed for the initial silicate hydration peak, as the coatings may limit the access of water to silicate phases [41]. Many researchers have found that prehydration not only decreases the magnitude of the main hydration peak but also delays it [10,12,23,37,41,42]. This was not consistently the case here for the treated cements, where the main hydration peak occurred earlier in some instances, especially after extended aging of 4 weeks and beyond (Figure 11).…”
Section: Paste Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…They also attribute these coatings to the lower values observed for the initial silicate hydration peak, as the coatings may limit the access of water to silicate phases [41]. Many researchers have found that prehydration not only decreases the magnitude of the main hydration peak but also delays it [10,12,23,37,41,42]. This was not consistently the case here for the treated cements, where the main hydration peak occurred earlier in some instances, especially after extended aging of 4 weeks and beyond (Figure 11).…”
Section: Paste Calorimetrymentioning
confidence: 99%
“…In earlier studies, oleic acid showed some promise, but concrete made with cement treated in this way suffers from decreased strength, which is attributed to a resultant increase in entrained air content [34,35]. Others have focused on changes in the performance of admixtures when batching concrete with prehydrated cement [36][37][38], evolving into new strategies where superplasticizing or retarding admixtures are specifically used to help mitigate problems associated with prehydration [39][40][41][42]. Similar approaches using superplasticizers have been implemented with calcium aluminate and calcium sulfoaluminate cements [43] that also are highly susceptible to prehydration [44,45].…”
Section: Introductionmentioning
confidence: 99%